Pengembangan dan validasi nutrient rich food index sebagai alat ukur kualitas konsumsi pada mahasiswa Fakultas Ilmu Kesehatan - Ekaningrum, Annisa Yuri (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The nutrient-rich food (NRF) index was developed as a nutrient profiling system that ranks foods based on their nutrient content. The NRF index was validated using the Healthy Eating Index (HEI) as the gold standard for evaluating adherence to dietary guidelines. In Indonesia, HEI was developed as a balance diet index (BDI).Objectives: This study aimed to analyze sociodemographic characteristics, consumption patterns, and determine which NRF is highly valid among students in the Health Science Faculty, Universitas Indonesia Maju.Methods: This study used cross-sectional study design. Simple random sampling involving 267 students was used. Data were analyzed using univariate and bivariate analysis. The NRF index was validated using the BDI3-60 as the gold standard.Results: The average energy intake is 1401,14 kilocalories, protein 610,16 g, fat 49,54 g, carbohydrate 194,13 g, vitamin A 105,97 microgram, dan vitamin C 34,7 mg. The food groups that had the most food items consumed by students were snacks. There was a significant relationship between NRF 9,3 (p=0,043) and NRF 11,3 (p=0,042) index scores and BDI3-60. Nevertheless, there was a very weak correlation coefficient for the relationship between NRF 6,3 (r=0,116), NRF 9,3 (r=0,123), and NRF 11,3 (r=0,124) with BDI3-60.Conclusion: There is significant correlation between Nutrient Rich Food (NRF) and the Index of Balanced Nutrition, but Nutrient Rich Food (NRF) shows a weak correlation with BDI3-60.KeywordsDiet quality, NRF index, student